POLA SPASIAL KAWASAN PERUMAHAN SERTA KETERSEDIAAN FASILITAS PENDUKUNG DI KECAMATAN CIANJUR - Nur Aeni; Lia Warlina (Tesa Arsitektur, 2023)
The Cianjur District's population has grown over the past ten years, which has raised the demand for livable housing and services to support the daily activities of the residents. This study aims to pinpoint the spatial pattern of residential areas and its impact as well as to ascertain whether Cianjur District has access to facilities for education, health and shopping. This study employed a quantitative descriptive method that combined map overlay analysis techniques with nearest neighbor analysis to analyze spatial patterns. The study's findings indicate that while only seven formal housing complexes available in 2010, there were a total of 29 housing complex were available after ten years. In the Cianjur District, residential land use construction reached 29.70% in 2010 and 49.27% in 2020. Primary school educational facilities are arranged in clusters, junior high schools in dispersion, and high schools in dispersion patterns. The spatial pattern of the puskesmas healthcare facilities is dispersed, with clinics and pharmacies arranged in clustered. All sections of the Cianjur District have access to health facilities' services. However, some formal housing estates have not been covered spatially by pharmacy services. The spatial pattern of shopping facilities is clustered, but residents in Cianjur District can still reach these facilities